FAKTOR YANG BERPENGARUH TERHADAP PENDAPATAN LEMBAGA KURSUS BAHASA ASING (Di Kawasan Kampung Bahasa Studi Desa Tulungrejo, Kecamatan Pare, Kabupaten Kediri) - Helmi Nurohman; Arfida Boedirochminarni (Jurnal Ilmu Ekonomi, 2020)
This research uses descriptive research type with quantitative approach. This research was conducted in the Kampung Bahasa Area, Tulungrejo Village with a population of 98 foreign language course institutions. The sample in this study were 50 respondents taken through probability sampling techniques. While data collection techniques use interviews, questionnaires, and documentation. The variables used in this study include venture capital (X1), business duration (X2), working hours (X3) and foreign language course institution income (Y). Analysis of the data used is multiple linear regression (OLS) with a significance level of 5%.The results showed that the independent variables partially influenced the dependent variable. The venture capital variable partially has a significant effect on the income of foreign language course institutions. The length of business variable partially has a significant effect on the income of foreign language course institutions, and working hours partially does not significantly influence the income of course institutions. The effect of the independent variable on the dependent variable in the study is 80.5% and the remaining 19.5% is explained by the variable other variables.